Dysfunctional overnight memory consolidation in ecstasy users. (August 2014) - Smithies, Vanessa; Broadbear, Jillian; Verdejo-Garcia, Antonio; Conduit, Russell
Sleep plays an important role in the consolidation and integration of memory in a process called overnight memory consolidation. Previous studies indicate that ecstasy users have marked and persistent neurocognitive and sleep-related impairments. We extend past research by examining overnight memory consolidation among regular ecstasy users ( n =12) and drug naïve healthy controls ( n =26). Memory recall of word pairs was evaluated before and after a period of sleep, with and without interference prior to testing. In addition, we assessed neurocognitive performances across tasks of learning, memory and executive functioning. Ecstasy users demonstrated impaired overnight memory consolidation, a finding that was more pronounced following associative interference. Additionally, ecstasy users demonstrated impairments on tasks recruiting frontostriatal and hippocampal neural circuitry, in the domains of proactive interference memory, long-term memory, encoding, working memory and complex planning. We suggest that ecstasy-associated dysfunction in fronto-temporal circuitry may underlie overnight consolidation memory impairments in regular ecstasy users.